THE EFFECT OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT D’BESTO CHICKEN & BURGER RESTO MARDANI RAYA CENTRAL JAVA - sunyoto, teguh (JURNAL ASIK, 2024)
The purpose of this study was to determine the effect of compensation and work environment on employee performance at Resto D'Besto Chicken & Burger Mardani Raya Central Jakarta. The research method used in this study uses a quantitative approach. The population is 41 people. The sampling technique uses saturated samples so that the number of samples in this study is 41 respondents. The data analysis technique uses multiple regression. The results of the study show that: (1) There is a positive and significant effect of compensation variables on employee performance at Resto D'Besto Chicken & Burger Mardani Raya Central Jakarta. This is evidenced by the t count> t table value, namely 7.325> 2.024 with a probability value (significance) = 0.000, which is below 0.05. (2) There is a positive and significant effect of work environment variables on employee performance at Resto D'Besto Chicken & Burger Mardani Raya Central Jakarta. This is proven by the value of t count > t table, which is 6.304 > 2.024 with a probability value (significance) = 0.000 which is below 0.05. (3) There is a positive and significant influence of compensation and work environment variables together on employee performance at Resto D'Besto Chicken & Burger Mardani Raya Central Jakarta. This is proven by the value of F count > F table, which is 28.299 > 3.24.